The Effectiveness of Parents Roles in Children's Sex Education - Andiana, Yosi Armelia; Slameto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Sexual offenses are not new, they have been happening for a long time and continue to happen every year, even in Indonesia. Not only experienced by adults, but also teenagers and even minors are getting sexually abused and assaulted by the predator.  According to reports, children and girls are more prone to get sexual harassment, with many occurrences remaining unreported due to fear, stigma for the victims, and a lack of understanding. One of the most effective preventive measures is sex education, which aims to equip children with knowledge and skills. However, discussions about sex are considered misinformation and social taboos, often disguised, a clear understanding of what constitutes good sex education is crucial. In this case family especially parents have responsibility as the first environment for the children to shape their children knowledge, attitude, behaviour and life skill about sexual topic through sex education. The The aim of this study is: to identifying  how effective the implement of the parent’s roles  as far. The method that used in this study is a literature review. The study was carried out based on 10 selected sources and analyzed. As a result, the conclusion point is concluded. From the overall resources used to assess the effectiveness of the parental role, the results show that the implementation is moderate to low in achieving the desired results. This ineffectiveness is evidenced by the moderate to low results on children. However, sex education is one of those things that cannot be addressed or taught only once; instead, it must be a continuous process to know the children. In other the other hand the parents can imply: 1. Balance engagement to support each other to be effective, 2. Create and build open communication, and 3. Collaborate with the school and teacher. From that, hopefully sex education can have a good influence on children's understanding, attitudes, and how they behave in respondin